Mengapa Minat Belajar Siswa dalam PAI Rendah? Analisis dan Strategi Peningkatan - Ashila Arasy; Diena Qaulan Tsaqila; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2025)
Student learning interest in Islamic Religious Education (PAI) currently shows a fairly low trend, characterized by a lack of active student involvement and low learning outcomes. This article aims to analyze the factors causing students' low learning interest in Islamic Education and offer various strategies for improvement. The influencing factors include monotonous teaching approaches, lack of family support, the influence of the social environment, a curriculum that is considered less relevant, and the lack of utilization of technology in learning. This research uses a descriptive qualitative method by collecting data from relevant literature. The results of the discussion show that to increase students' interest in learning, a more varied approach is needed such as the use of interactive learning media, technology integration, parental involvement, project-based learning, class discussions, and the creation of a positive learning environment. By implementing these strategies, it is expected that students' interest in learning PAI can increase significantly.